Morning Activity dan Implikasinya Terhadap Habituasi Infaq dan Shadaqah serta Penguatan Karakter Peduli Sosial Siswa SMP Muhammadiyah Plus Salatiga - Amalina Rizqi Rahmawati; Mukh Nursikin (Institut Islam Nahdlatul Ulama Temanggung, 2021)
The purpose of the education can be activity with optimal result, if operated with appropriate strategy. One of the appropriate strategy to help the purpose of education can be achieve is morning activity. Activities in the morning before to beginning of teaching. For giving good habituation in students self. The purpose of the research are (1) to describe morning activity in Muhammadiyah Plus Junior High School Salatiga; (2) to describe morning activity implication to give clarity habituation in Muhammadiyah Plus Junior High School Salatiga; and (3) to describe morning activity implication to increase take care for each other in Muhammadiyah Plus Junior High School Salatiga. The methodology of this research is field research and the subjects are teachers of Muhammadiyah Plus Junior High School Salatiga. The data collection uses interview technique, observation, and documentation. The result of this research are as follows: (1) morning activity are activity in the morning befpre the beginning to teaching such as dhuha prayers together, tadarus, tahfizh, morning motivation, give clarity, and morning ceremony; (2) morning activity implication to give clarity hatituation such as student active to give for help the each other; and (3) morning activity implication to increase take care for each other are student can emphaty to other people, take care to friends, follows on social event, respect to teachers and staffs.